Development of Next-Generation Peptide Binders Using In vitro Display Technologies and Their Potential Applications - Wada, Akira (Frontiers in Immunology, 2013)
During the last decade, a variety of monoclonal antibodies have been developed and used as molecular targeting drugs in medical therapies. Although antibody drugs tend to have intense pharmacological activities and negligible side effects, several issues in their development and prescription remain to be resolved. Synthetic peptides with affinities and specificities for a desired target have received significant attention as alternatives to antibodies. In vitro display technologies are powerful methods for the selection of such peptides from combinatorial peptide libraries. Various types of peptide binders are being selected with such technologies for use in a wide range of fields from bioscience to medicine. This mini review article focuses on the current state of in vitro display selection of synthetic peptide binders and compares the selected peptides with natural peptides/proteins to provide a better understanding of the target affinities and inhibitory activities derived from their amino acid sequences and structural frameworks. The potential of synthetic peptide binders as alternatives to antibody drugs in therapeutic applications is also reviewed.